University Students’ Views on the Perceived Benefits and Drawbacks of Seeking Help for Mental Health Problems on the Internet: A Qualitative Study - Chan, Jade KY (JMIR Hum Factors, 2016)
BACKGROUND: University students experience high levels of mental health problems yet very few seek professional help. Web-based mental health interventions may be useful for the university student population. However, there are few published qualitative studies that have examined the perceived benefits and drawbacks of seeking help for mental health problems on the Internet from the perspective of university students. OBJECTIVE: To investigate the attitudes of university students on mental health help-seeking on the Internet. METHODS: A total of 19 university students aged 19-24 years participated in 1 of 4 focus groups to examine their views toward help-seeking for mental health problems on the Internet. RESULTS: Perceived concerns about Web-based help-seeking included privacy and confidentiality, difficulty communicating on the Internet, and the quality of Web-based resources. Potential benefits included anonymity/avoidance of stigma, and accessibility. Participants reported mixed views regarding the ability of people with similar mental health issues to interact on the Internet. CONCLUSIONS: These factors should be considered in the development of Web-based mental health resources to increase acceptability and engagement from university students.